2008
DOI: 10.1029/2008jd009861
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and seasonal concentration change of methyl iodide in the atmosphere

Abstract: We investigated seasonal variations in atmospheric CH3I at high, middle, and low latitudes in both hemispheres: at Alert (82.5°N, 62.5°W), over the northern and western Pacific Ocean (shipboard measurements); Cape Ochiishi (43.2°N, 145.5°E); Tsukuba (36.0°N, 140.1°E); Happo Ridge (36.7°N, 137.8°E); Hateruma Island (24.1°N, 123.8°E); San Cristobal Island (1.0°S, 89.4°W); Cape Grim (40.4°S, 144.6°E); and Syowa Station in Antarctica (68.5°S, 41.3°E) throughout 2004 and over an extended period of years at some sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 40 publications
10
64
0
Order By: Relevance
“…The spatial disconnect between atmospheric IO and the Chl-a concentration, however, poses questions about which iodine emissions can legitimately be scaled using Chl-a distributions. Notably, some of the highest CH 3 I concentrations observed are found over the Eastern Pacific ocean (34), where deep convection also provides a transport pathway into the FT. The apparent correlation between satellite IO and Chl-a could possibly be because of the coupled effect of biological sources producing IO precursors with a longer lifetime and dynamical impacts on their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial disconnect between atmospheric IO and the Chl-a concentration, however, poses questions about which iodine emissions can legitimately be scaled using Chl-a distributions. Notably, some of the highest CH 3 I concentrations observed are found over the Eastern Pacific ocean (34), where deep convection also provides a transport pathway into the FT. The apparent correlation between satellite IO and Chl-a could possibly be because of the coupled effect of biological sources producing IO precursors with a longer lifetime and dynamical impacts on their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Among the organic source gases, methyl iodide (CH 3 I) is the generally most abundant one due to its comparatively long atmospheric lifetime of ∼7 days and due to sizable emissions from algae and oceanic surface waters (WMO-2006). Measurements in marine boundary layer air indicate that background CH 3 I concentrations range between 0.1 ppt and 2 ppt (Butler et al, 2007;Yokouchi et al, 2008) with higher values reported from North Atlantic coastal source regions (e.g. Peters et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Methyl iodide is a very short-lived species (1-2 d) with a major oceanic source (Yokouchi et al, 2008) and minor terrestrial sources (e.g., Redeker et al, 2003;Sive et al, 2007). Its mixing ratio declined sharply with altitude, consistent with its short atmospheric lifetime (Fig.…”
Section: Minimally Enhanced Halocarbonsmentioning
confidence: 99%